The determinants of dividend policy: evidence from foods and beverages listed companies in Bursa Malaysia / Nurul Aqila Kamaruddin - Kamaruddin, Nurul Aqila (2019)
There are many countries that have implemented the dividend policy in the various sector. This study observed about the factors that influence the dividend policy of food and beverage companies in Malaysia. The total samples that have been used in this study are 26 companies of food and beverage listed in Bursa Malaysia for each period. Pooled Ordinary Least Square Model has been selected in this study with the data collected 2008 until 2017 based on the Thomson Eikon Retuers and annual report of food and beverage companies. This study aims to examine the determinants of dividend policy on food and beverage companies as well as to determine the most significant factors that influence the dividend policy. These studies shows that profitability, liquidity and market capitalization has positive relationship while the other variables which include leverage, investment opportunity and size of the firm shows negative relationship toward dividend policy. The result finding shows three variables highly significant level of 1% with dividend payout ratio. In conclusion, the finding shows clearly explanation of the determinant of food and beverage sector in Malaysia.